Deep Learning Strengthens Religious Moderation Attitudes in Madrasah Students - Nabiilah, Zayyin; Arifin, Nuzulul Rizqi (Indonesian Journal of Education Methods Development, 2026)
General Background: Religious moderation constitutes a strategic priority in Islamic education, requiring pedagogical approaches that cultivate tolerant, balanced, and contextual religious understanding among students in pluralistic societies. Specific Background: At MTs Darul Hikmah Sidoarjo, deep learning has been implemented in Islamic Religious Education (PAI) to encourage reflective, dialogical, and contextual engagement with religious values. Knowledge Gap: Although deep learning is theoretically aligned with constructivist and meaningful learning principles, limited empirical description exists regarding its classroom implementation in madrasah settings and its relation to students’ religious moderation attitudes. Aims: This study aims to describe the implementation of deep learning and analyze its contribution to strengthening students’ religious moderation attitudes. Results: Using a qualitative case study design with observation, interviews, and documentation, the findings indicate that problem-based learning, group dialogue, religious reflection, and analytical assignments foster deeper conceptual understanding of moderation values, including tolerance, justice, balance, and respect for differences. The study also reports increased openness toward diverse opinions, stronger commitment to fairness in religious practice, and reduced narrow fanaticism. Novelty: This research provides an in-depth qualitative account linking deep learning strategies with the internalization of religious moderation attitudes in a madrasah context. Implications: The findings recommend sustained integration of deep learning in PAI instruction to cultivate critical thinking, reflective awareness, and moderate religious character among secondary-level students. Highlights: Reflective and problem-oriented instruction promotes tolerance and fairness in classroom religious discourse. Dialogical activities cultivate balanced perspectives and respect for socio-religious diversity. Analytical and contextual tasks reduce narrow fanatic tendencies among eighth-grade learners. Keywords: Deep Learning, Religious Moderation, Islamic Religious Education, Madrasah Education